Socially Responsible Surgery: Building Recognition and Coalition - Robinson, Tyler D.; Oliveira, Thiago M.; Timmes, Theresa R.; Mills, Jacqueline M.; Starr, Nichole; Fleming, Matthew; Janeway, Megan; Haddad, Diane; Sidhwa, Feroze; Macht, Ryan D.; Kauffman, Douglas F.; Dechert, Tracey A. (Frontiers in Surgery, 2017)
Importance: Socially Responsible Surgery (SRS) integrates surgery and public health, providing a framework for research, advocacy, education and clinical practice to address the social barriers of health that decrease surgical access and worsen surgical outcomes in underserved patient populations. These patients face disparities in both health and in healthcare, which can be effectively addressed by surgeons in collaboration with allied health professionals. Objective: We reviewed the current state of surgical access and outcomes of underserved populations in American rural communities, American urban communities, and in low- and middle- income countries. Evidence review: We searched PubMed using standardized search terms, and reviewed the reference lists of highly relevant articles. We reviewed the reports of two recent global surgery commissions. Conclusions: There is an opportunity for scholarship in rural surgery, urban surgery and global surgery to be unified under the concept of SRS. The burden of surgical disease and the challenges to management demonstrate that achieving optimal health outcomes requires more than excellent perioperative care. Surgeons can and should regularly address the social determinants of health experienced by their patients. Formalized research and training opportunities are needed to meet the growing enthusiasm among surgeons and trainees to develop their practice as socially responsible surgeons.□